2015
DOI: 10.1371/journal.pone.0117105
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emotional Events that People Ruminate about Feel Closer in Time

Abstract: Rumination is intrusive, perseverative cognition. We suggest that one psychological consequence of ruminating about negative emotional events is that the events feel as though they happened metaphorically “just yesterday”. Results from three studies showed that ruminating about real world anger provocations, guilt-inducing events, and sad times in the last year made these past events feel as though they happened more recently. The relationship between rumination and reduced temporal psychological distance pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…For experiments using music, participants in the control group will often not listen to music, or music that induces a different emotion (e.g., Sharman & Dingle, 2015). Researchers using autobiographical recall often ask participants to think or write about an instance(s) from their past when they experienced an ordinary event (e.g., an interaction with a stranger; Siedlecka, Capper, & Denson, 2015). Control groups for situational procedures usually retain the social aspect of the paradigm, but remove the emotion-eliciting aspect (e.g., writing an essay and receiving neutral, rather than positive or negative feedback; Bushman & Baumeister, 1998).…”
Section: Control Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…For experiments using music, participants in the control group will often not listen to music, or music that induces a different emotion (e.g., Sharman & Dingle, 2015). Researchers using autobiographical recall often ask participants to think or write about an instance(s) from their past when they experienced an ordinary event (e.g., an interaction with a stranger; Siedlecka, Capper, & Denson, 2015). Control groups for situational procedures usually retain the social aspect of the paradigm, but remove the emotion-eliciting aspect (e.g., writing an essay and receiving neutral, rather than positive or negative feedback; Bushman & Baumeister, 1998).…”
Section: Control Groupsmentioning
confidence: 99%
“…Researchers often ask participants to think or write about an instance(s) from their past when they experienced anger. The idea is that recall will reactivate the anger, thereby causing participants to relive the anger (e.g., Siedlecka et al, 2015). Numerous studies using autobiographical recall observed significant self-reported anger responses, and significantly increased physiological responses such as heart rate, skin conductance, and systolic blood pressure (e.g., Marci, Glick, Loh, & Dougherty, 2007).…”
Section: Autobiographical Recallmentioning
confidence: 99%
“…Moreover, we adopted the same measure for psychological distance across the three studies. Although the adopted measure has been widely used previously (Ross & Wilson, 2002;Siedlecka, Capper, & Denson, 2015;Van Boven et al, 2010), it is important to replicate the findings using another measure. To overcome these limitations, we conducted Study 4.…”
Section: Studymentioning
confidence: 99%
“…Future research should explore additional mechanisms accounting for these patterns. For instance, negative memories that feel close may also prompt rumination, inhibit forgiveness, activate memories of other unrelated past transgressions, foster stable attributions, or create worry that history could repeat itself (Cortes & Wilson, 2016;Haddock, 2004;Siedlecka, Capper, & Denson, 2015;Wohl & McGrath, 2007).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%